Tarachime - Kawase, Naomi (Kumie ; Arte France Cinema, 2006)
Verzio FF Submission A autobiographical documentary where the filmmaker records moments in her life without being afraid to expose very intimate moments such as nudity, bathing, giving birth or breast feeding. When recording the death of her grandmother and, at the same time, the birth of her son, the filmmaker reflects on the cyclical nature of life.